Combined targeting of high‐mobility group box‐1 and interleukin‐8 to control micrometastasis potential in gastric cancer. Issue 7 (16th April 2015) - Chung, Hye Won; Jang, Sunphil; Kim, Hoguen; Lim, Jong‐Baeck
<x xml:space="preserve">Abstract</x> Micrometastasis is the major cause of treatment failure in gastric cancer (GC). Because epithelial‐to‐mesenchymal transition (EMT) is considered to develop prior to macroscopic metastasis, EMT‐promoting factors may affect micrometastasis. This study aimed to evaluate the role of extracellular high‐mobility group box‐1 (HMGB1) in EMT and the treatment effect of combined targeting of HMGB1 and interleukin‐8 (IL‐8) at early‐stage GC progression through interrupting EMT promotion. Extracellular HMGB1 was induced by human recombinant HMGB1 and pCMV‐SPORT6‐HMGB1 plasmid transfection. EMT activation was evaluated by immunoblotting, immunofluorescence and immunohistochemistry. Increased migration/invasion activities were evaluated by in vitro transwell migration/invasion assay using all histological types of human GC cell lines (N87, MKN28 SNU‐1 and KATOIII), N87‐xenograft BALB/c nude mice and human paired serum‐tissue GC samples. HMGB1‐induced soluble factors were measured by chemiluminescent immunoassay. Inhibition effects of tumor growth and EMT activation by combined targeting of HMGB1 and IL‐8 were evaluated in N87‐xenograft nude mice. Serum HMGB1 increases along the GC carcinogenesis and reaches maximum before macroscopic metastasis. Overexpressed extracellular HMGB1 promoted EMT activation and increased cell motility/invasiveness through ligation to receptor for advanced glycation end products. HMGB1‐induced IL‐8 overexpression contributed the HMGB1‐induced EMT in GC in vitro and in vivo. Blocking HMGB1 caused significant reduction of tumor growth, and addition of human recombinant IL‐8 rescues this antitumor effects. Our results imply the role of HMGB1 in EMT through IL‐8 mediation, and a potential mechanism of GC micrometastasis. Our observations suggest combination strategy of HMGB1 and IL‐8 as a promising diagnostic and therapeutic target to control GC micrometastasis.